IMPLEMENTASI KONSEP PENDIDIKAN KARAKTER KI HAJAR DEWANTARA DI SMP NEGERI 2 BOJONEGORO - Fauziatun Nisa’, Ida; Miftah, Zaini (Universitas Nahdlatul Ulama Sunan Giri, 2021)
in this increasingly modern and growing age, especially in technological systems Communication and information, and the mindset of age children grows Adolescence or puberty. To compensate for it all so that the child will not be distracted by it Technological advances are more sophisticated, and children's character education needs attention, Whether in the family circle, school, or community. This research is meant to know Ki Hajar Dewantara character education concepts and implementation in public junior high school 2